Analisis Faktor Penyebab Rendahnya Penerimaan Zakat Perusahaan di Indonesia - Prasasti Nuraeni Sasti; Zulkarnain Muhammad Ali; Indra (IRTIQO' : Postgraduate Journal of Islamic Economics, Finance and Accounting Studies, 2023)
Background – Indonesia has a very high potential for corporate zakat, in fact the potential for corporate zakat is the highest potential among other sources of zakat. Until 2020, the company's zakat potential will reach 144.5 trillion based on data obtained from the Baznas Strategic Studies Center (Puskas Baznas), but ironically, the company's zakat receipts are actually very small and not directly proportional to its huge potential. Therefore, it is necessary to carry out an in-depth analysis to find out what factors influence why corporate zakat receipts in Indonesia are still so low.. Objective - This research aims to analyze what factors influence the company's low zakat receipts both from an internal and external perspective of the company as well as to find criteria and recommendations for the best solutions that have the strongest influence that can be used to overcome these problems. Research Method - The analytical method in this study uses the Analytic Network Process (ANP) with the help of super decisions software as a decision making tool. The data sources in this research come from primary data and secondary data. Primary data was obtained from interviews with respondents consisting of zakat practitioners, regulators and academics. Meanwhile, secondary data was obtained from the results of a review of relevant previous research literature. Findings - The first results of this research resulted in the finding that the internal factors that cause the company's low zakat receipts in Indonesia are mainly the company's low knowledge and understanding of the existence of zakat obligations, while in terms of external factors the main problem that is most influential is the government's still low support for zakat management system in Indonesia. The second finding resulted in a priority solution to overcome the problem of low company zakat receipts in terms of the most important internal problem, namely by providing tax incentives for companies that have paid their zakat obligations. Meanwhile, the priority for solving external problems is increasing government support and strengthening the system. Keywords: Corporate Zakat, Problem, Solutions